Exercise and Coronary Atherosclerosis: Observations, Explanations, Relevance, and Clinical Management - Aengevaeren, Vincent L; Mosterd, Arend; Sharma, Sanjay; Prakken, Niek H J; Möhlenkamp, Stefan; Thompson, Paul D; Velthuis, Birgitta K; Eijsvogels, Thijs M H (Circulation (New York, N.Y.), 2020)
Physical activity and exercise training are effective strategies for reducing the risk of cardiovascular events, but multiple studies have reported an increased prevalence of coronary atherosclerosis, usually measured as coronary artery calcification, among athletes who are middle-aged and older. Our review of the medical literature demonstrates that the prevalence of coronary artery calcification and atherosclerotic plaques, which are strong predictors for future cardiovascular morbidity and mortality, was higher in athletes compared with controls, and was higher in the most active athletes compared with less active athletes. However, analysis of plaque morphology revealed fewer mixed plaques and more often only calcified plaques among athletes, suggesting a more benign composition of atherosclerotic plaques. This review describes the effects of physical activity and exercise training on coronary atherosclerosis in athletes who are middle-aged and older and aims to contribute to the understanding of the potential adverse effects of the highest doses of exercise training on the coronary arteries. For this purpose, we will review the association between exercise and coronary atherosclerosis measured using computed tomography, discuss the potential underlying mechanisms for exercise-induced coronary atherosclerosis, determine the clinical relevance of coronary atherosclerosis in middle-aged athletes and describe strategies for the clinical management of athletes with coronary atherosclerosis to guide physicians in clinical decision making and treatment of athletes with elevated coronary artery calcification scores.